Wetland response to sedimentation and nitrogen loading: diversification and inhibition of nitrogen-fixing microbes - Moseman-Valtierra, S M; Armaiz-Nolla, K; Levin, L A (Ecological applications, 2010)
Anthropogenic inputs of nutrients and sediment simultaneously impact coastal ecosystems, such as wetlands, especially during storms. Independent and combined effects of sediment and ammonium nitrate loading on nitrogen fixation rates and diversity of microbes that fix nitrogen (diazotrophs) were tested via field manipulations in Spartina foliosa and unvegetated zones at Tijuana Estuary (California, USA). This estuary is subject to episodic nitrogen enrichment and sedimentation associated with rain-driven flooding and slope instabilities, the latter of which may worsen as the Triple Border Fence is constructed along the U.S.-Mexico border. Responses of diazotrophs were assessed over 17 days using acetylene reduction assays and genetic fingerprinting (terminal restriction fragment length polymorphism [T-RFLP]) of nifH, which codes for dinitrogenase reductase. Sulfate-reducing bacteria performed approximately 70% of nitrogen fixation in Spartina foliosa rhizospheres in the absence of nitrogen loading, based on sodium molybdate inhibitions in the laboratory. Following nutrient additions, richness (number of T-RFs [terminal restriction fragments]) and evenness (relative T-RF fluorescence) of diazotrophs in surface sediments increased, but nitrogen fixation rates decreased significantly within 17 days. These responses illustrate, within a microbial community, conformance to a more general ecological pattern of high function among assemblages of low diversity. Diazotroph community composition (T-RF profiles) and rhizosphere diversity were not affected. Pore water ammonium concentrations were higher and more persistent for 17 days in plots receiving sediment additions (1 cm deep), suggesting that recovery of diazotroph functions may be delayed by the combination of sediment and nutrient inputs. Nitrogen fixation constitutes a mechanism for rapid transfer of fixed N to S. foliosa roots and a variety of primary consumers (within 3 and 8 days, respectively), as determined via 15N2 enrichment studies with in situ microcosms of intact marsh sediment. Thus, long-term declines in nitrogen fixation rates in response to increasingly frequent nutrient loading and sedimentation may potentially alter nitrogen sources for vascular plants as well as trophic pathways in wetland ecosystems.